Penyuluhan Penanggulan Stunting Pada Ibu Hamil dan Yang Memiliki Balita Di Desa Pariksinomba Kecamatan Dolok Sanggul Tahun 2024 - Simamora, Debora Natalia; Sihite, Helprida (Cattleya Darmaya Fortuna, 2024)
Stunting is a condition of failure to thrive in children due to chronic malnutrition which has an impact on children's physical and cognitive development and threatens the quality of human resources in the future. This counseling on stunting prevention for pregnant women and mothers with toddlers aims to increase understanding and practice regarding providing proper nutrition and health care during pregnancy and the early stages of a child's life. Outreach activities are carried out through interactive lecture methods, group discussions, and the distribution of educational materials covering the importance of balanced nutrition, exclusive breastfeeding practices, and handling diseases in toddlers. The results of this activity show increased knowledge and changes in behavior among mothers to support optimal child growth and development. By increasing education and nutritional awareness among pregnant women and mothers of toddlers, it is hoped that the stunting rate can be reduced significantly and create a healthy and high-quality generation. Keywords: Stunting, counseling, pregnant women, mothers of toddlers